Analysis of Urinary Midkine and Volatile Organic Compound (VOC) Levels Using a Breath Analyzer for Screening and Early Diagnosis of Lung Cancer - Mafisah, Saidah; Setyawan, Ungky Agus; Tantular, Rezki; Permana, Deden; Djajalaksana, Susanthy; Wardoyo, Arinto Yudi Ponco; Listyoko, Aditya Sri (Jurnal Respirasi, 2025)
Introduction: Lung cancer is the leading cause of cancer-related mortality worldwide. Midkine, a heparin-binding growth factor, promotes proliferation, angiogenesis, and metastasis. Volatile organic compounds (VOCs) reflect cellular and molecular changes, aiding in cancer diagnosis. This study explored urinary midkine and VOC profiles as biomarkers for lung cancer screening and early diagnosis. Methods: A case-control, cross-sectional study was conducted on 20 controls (family members of lung cancer patients) and 20 lung cancer patients who had not received therapy. Volatile organic compounds breath analysis and urinary midkine measurements were performed. Volatile organic compounds, including total volatile organic compounds (TVOCs), ethanol (C2H5OH), formaldehyde (CH2O), toluene (C7H8), acetone (C3H6O), hexane (C6H14), and methane (CH4), were collected from exhaled breath using Tedlar bags and measured with a µβreath analyzer. Meanwhile, urinary midkine levels were determined using the Enzyme-Linked ImmunoSorbent Assay (ELISA) method. Statistical analyses included an independent t-test, Mann-Whitney U test, Spearman correlation, and diagnostic testing with receiver operating characteristic (ROC) analysis. Results: Urinary midkine levels were higher in lung cancer patients than in controls (330.56±120.50 vs. 282.18±146.28 pg/mL), although not significant (p>0.05). The independent t-test revealed that ethanol levels were significantly elevated in lung cancer patients (p < 0.001), whereas methane levels were not (p > 0.50). Receiver operating characteristic analysis demonstrated sensitivity and specificity: urinary midkine (60%, 60%), ethanol (75%, 75%), and methane (45%, 45%). Conclusion: Ethanol VOC appears to be a promising non-invasive biomarker for the early detection of lung cancer, whereas elevated urinary midkine levels did not demonstrate significant diagnostic value.